ANALYSIS OF COMPETING INTERESTS IN THE KARTU PETANI BERJAYA POLICY FOR SUSTAINABLE COMMUNITY AGRICULTURAL DEVELOPMENT IN LAMPUNG PROVINCE - Riky Fernando; Muhammad Ibnu; Helvi Yanfika; Kordiyana K. Rangga; Indah Listiana (PT. Jurnal Center Indonesia Publisher, 2025)
This study analyzes the competing interests within the Kartu Petani Berjaya (KPB) policy as part of efforts to promote sustainable community-based agricultural development in Lampung Province. The KPB program was launched with the goal of improving farmers' welfare through digitally integrated agricultural services. However, initial observations indicate resistance from some farmers and signs of political interest dominance in both the formulation and implementation processes. The study aims to identify the political motives behind the policy, the sustainability of the program, farmers' literacy regarding the E-KPB system, and the extent to which the program empowers farmers and engages stakeholders. Using a descriptive qualitative approach with thematic analysis and source triangulation techniques, data were collected through in-depth interviews with academics and government officials, as well as document studies. The findings reveal that the dominance of regional leaders in decision-making has led to a program orientation that is more symbolic and electoral in nature. The dynamics of competing interests emerge both vertically and horizontally, resulting in weak coordination and reduced policy effectiveness. The transition from KPB to E-KPB has also shifted the program’s focus and reduced its tangible benefits for farmers. The study recommends strengthening multi-stakeholder collaborative governance in agricultural policy, reevaluating the structure of the E-KPB system, and actively involving academics and farmer associations. These findings contribute theoretically to the study of public policy and policy framing, and practically to improving the implementation of programs based on the real needs of farming communities.